Asuhan Keperawatan Gerontik Pada Pasien Gout Arthritis Dengan Pemberian Intervensi Kompres Jahe Untuk Mengurangi Tingkat Nyeri Di Panti Werdha Kasih Ayah Bunda - Siti Sopiah; Siti Robeatul Adawiyah; Rina Puspita Sari; Siti Rahayu (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Elderly is a closing period in a person's life span, namely a period when a person has moved from a more useful and productive time. With increasing age, physiological function decreases due to the aging process so that joint disease appears in the elderly. One of the joint diseases in the elderly is gout arthritis. There are two ways to reduce uric acid, pharmacological and non-pharmacological. Non-pharmacological can be done by giving ginger compresses to reduce pain levels. Objective: The purpose of this paper is to determine the effectiveness of ginger compresses to reduce pain levels in the elderly with gout problems. Method: Case study design using nursing care. The case study sample used 1 patient. Results: Based on the implementation results on Mr. S with the application of ginger compress therapy for 7 days the pain scale decreased, the first and second days a pain scale of 5, on the third and fourth days a pain scale of 4, on the fifth and sixth days a pain scale of 2 and on the seventh day a pain scale of 1 with uric acid levels on day the first was 8 mg/dl and on the seventh day the uric acid level was 7.3 mg/dl, so a nursing diagnosis of chronic pain, it can be concluded that there is a change towards improvement, this shows the effect of giving ginger compresses on reducing pain levels.